Penggunaan Harta Waris Prapembagian Ditinjau dari Kompilasi Hukum Islam (KHI): Studi Kasus di Desa Paluh Kurau Kecamatan Hamparan Perak - Hidayah, Mhd. Fajri; Hasanah, Uswatun (AL-SULTHANIYAH, 2025)
This study discusses the practice of using property prior to inheritance, namely the possession or use of property carried out unilaterally by one of the heirs without the consent of the other heirs before the distribution of inheritance. This study was carried out to find out what factors caused some heirs in Paluh Kurau Village to use or control property before the distribution of inheritance and to find out the review of the law in KHI perspective. Qualitative research was applied in this study using an empirical method that used primary and secondary data sources. The primary data source is in the form of collecting data directly from the field through the results of interviews with the people of Paluh Kurau Village, then collected and used as a basis for analysis base on the Compilation of Islamic Law. Secondary data sources are books and articles related to inheritance. The results of the study concluded that some heirs in Paluh Kurau Village used their property before the distribution of inheritance and the cause was due to a lack of religious understanding, especially regarding inheritance issues, then some were due to the need for life or economy, and some were due to a lack of concern for other heirs. If analyzed from the Compilation of Islamic Law, then the practice of using property before the distribution of inheritance is inappropriate and contradictory, because legally each heir has the right to the property which must be divided according to their respective share so that the property cannot be used unilaterally without the consent of other heirs before an agreement in the distribution of inheritance occurs and each heir is aware or knows his share.